An On-the-Fly Surface-Hopping Program JADE for Nonadiabatic Molecular Dynamics of Polyatomic Systems: Implementation and Applications - Du, Likai; Lan, Zhenggang (Journal of chemical theory and computation, 2015)
Nonadiabatic dynamics simulations have rapidly become an indispensable tool for understanding ultrafast photochemical processes in complex systems. Here, we present our recently developed on-the-fly nonadiabatic dynamics package, JADE, which allows researchers to perform nonadiabatic excited-state dynamics simulations of polyatomic systems at an all-atomic level. The nonadiabatic dynamics is based on Tully's surface-hopping approach. Currently, several electronic structure methods (CIS, TDHF, TDDFT(RPA/TDA), and ADC(2)) are supported, especially TDDFT, aiming at performing nonadiabatic dynamics on medium- to large-sized molecules. The JADE package has been interfaced with several quantum chemistry codes, including Turbomole, Gaussian, and Gamess (US). To consider environmental effects, the Langevin dynamics was introduced as an easy-to-use scheme into the standard surface-hopping dynamics. The JADE package is mainly written in Fortran for greater numerical performance and Python for flexible interface construction, with the intent of providing open-source, easy-to-use, well-modularized, and intuitive software in the field of simulations of photochemical and photophysical processes. To illustrate the possible applications of the JADE package, we present a few applications of excited-state dynamics for various polyatomic systems, such as the methaniminium cation, fullerene (C20), p-dimethylaminobenzonitrile (DMABN) and its primary amino derivative aminobenzonitrile (ABN), and 10-hydroxybenzo[h]quinoline (10-HBQ).